Th1/Th2 Differentiation and B Cell Function by the Atypical PKCs and Their Regulators - Martin, Pilar; Moscat, Jorge (Frontiers in Immunology, 2012)
The members of the atypical PKCs (aPKC) kinase subfamily, PKCζ and PKCλ/ι, as well as their adapters, p62 and Par-6, form part of the PB1-domain-containing group of signaling regulators. Both adapters serve to locate through heterotypic interactions the aPKCs into the NF-κB and cell polarity pathways, respectively. Both signaling cascades have been critically implicated in T cell function in vitro and in vivo. The analysis of gene-knockout (KO) mice deficient in the different PB1 molecules is providing more definitive information on the actual role that the aPKCs and other PB1-containing molecules play in B cell biology and T cell polarity, survival and differentiation towards the different effector lineages in vivo and at the cellular ex vivo level. Here we discuss recent data generated from the analysis of KO mice linking the control of cell polarity by PKCλ/ι and PKCζ, their adapter p62, and the Par-4 inhibitor, in the control of B and T cell signaling and differentiation. Altogether, these genetic and biochemical evidences reveal the existence of a PB1-orchestrated signaling network that acts to control Th2-differentiation in vitro and in vivo, and the gene transcriptional programs that are essential during the B cell maturation and function and Th2 differentiation.